Comparative performance of calves from Bunaji (White Fulani) dams and Charolais, three-quarter Friesian and Bunaji sires - Johnson, A.O.; Bell, T.D. (Cambridge University Press, 1978)
Beef performance of the progeny of Bunaji dams mated to Charolais, Friesian crossbred and Bunaji bulls were investigated. The live weight and growth patterns of calves from Bunaji (White Fulani) cows sired by Charolais, three-quarters Friesian crossbreds and Bunaji bulls were observed in 2 years. Twelve steers per breed were evaluated on carcass merit after 250 days post-weaning feeding. The Charolais half-cross and Friesian three-eighth calves were heavier at birth, weaning and at 112 and 250 days than the Bunaji calves. The carcass data indicated superior slaughter weight and loin eye area in favour of the crossbreds. There were no differences for dressed weight, dressing percentage, carcass grade and hide weight percentage among the breed groups. Carcass retail cuts showed heavier sirloin steaks and round steaks in crossbreds. The results were indicative of the superior growth of crossbreds and underlined their carcass potential, which may be useful in upgrading the indigenous stock. Further work needed to confirm the present trends.